Image Analysis in Wood Testing - Selected Examples (Agricultural Engineering, 2016)
This paper is a review article which presents examples of application of the image analysis in wood testing. The objective of the paper was to present selected research methods with the use of image analysis used in the research on anatomy and macro-structure of wood carried out in the Department of Forest and Wood Utilization of the Institute of Forest Utilization and Forest Technology of the University of Agriculture in Krakow. In the part concerning research on wood anatomy the following areas of application of the image analysis were indicated: identification of wood species and variability of the selected parameters of the anatomic structure with special attention to coniferous trees. In the part concerning the research on macro-structure of wood, methodology of collection and preparation of wood samples and measurement of the most important properties of the macrostructure was described with the use of the image analysis program. Moreover, the selected areas of practical application of the results of such analysis were indicated.